Work-life balance in Greece: A State-of-The-Art Review - Anastasopoulou , Anna; Vraimaki, Eftichia; Trivellas, Panagiotis (The Greek Review of Social Research, 2024)
In today's working and living conditions, work-life balance (WLB) issues have come more forcefully to the foreground. This paper offers a state-of-the-art review of scholarly research on WLB in Greece from 2011 to 2021. Greece is an interesting case as it had to manage the side effects of a tremendous economic crisis and the disruptions caused by the pandemic and the war in Ukraine. The interdisciplinary character and the WLB determinants identified in empirical research are highlighted and discussed. The paper stresses the need to re-examine previous research to better understand WLB under the new realities and orient future research.